Digitalisasi Marketing dalam Upaya Peningkatan Penjualan pada UMKM Konveksi Topi Baret - Mochammad Hasan Sidqi; Laila Badriyah; Eli Masnawati; Rahayu Mardikaningsih; Mila Hariani; Didit Darmawan; Rommy Hardyansah (Lembaga Pengembangan Kinerja Dosen, 2024)
Companies today are faced with a variety of opportunities and threats. Entrepreneurs are starting to be pressured to innovate, minimize operational costs, and perform well in their business. An increase in sales can be said to be a series of activities to increase the release of products through buying and selling activities. This service aims to share a technology development to increase sales in the beret hat convection MSME business in Ngudi Hamlet, Punggul Village, Gedangan District, Sidoarjo Regency. The method used as basic research for this service activity is Participatory Action Research (PAR). The result of this activity is the establishment of Shopee and Tokopedia accounts that have been developed regarding business descriptions and photos of attractive products. The author emphasizes the spirit of entrepreneurship in the era of more and more competitors by utilizing social media and e-commerce.